Global drought risk in cities: present and future urban hotspots - Tristian R Stolte; Hans de Moel; Elco E Koks; Marthe L K Wens; Felix van Veldhoven; Snigdha Garg; Neuni Farhad; Philip J Ward (Environmental Research Communications, 2023)
Hydrological droughts pose a persistent threat for cities and are increasingly studied. However, this is rarely within a large-scale context, complicating comparisons between cities and potentially hampering the most efficient allocation of resources in terms of drought risk adaptation and mitigation. Here, we investigate global urban hydrological drought risk for 264 urban agglomerations across all continents for both the present time and future projections. To derive risk profiles for each agglomeration, we include components of: drought hazard (drought volume focusing on surface water deficits), exposure (urban population), vulnerability (multivariate vulnerability index), and cost (replacement of freshwater expenses). These components are dynamic in time, except for vulnerability. Most agglomerations are projected to experience an increase in drought hazard, exposure, and cost by 2050, with the most notable current and future hotspot being northern South Asia (India & Pakistan). Also, the number of agglomerations with high risk increases, whereas the number with lower risk decreases, indicating that high urban drought risk is increasing in scale over time. Our results enable a better targeting of those agglomerations that need most urgent attention in terms of drought risk solutions. It can also be used to identify agglomerations with similar drought risk profiles that could be studied in conjunction and may benefit from cooperative drought risk management strategies.